Vein mechanism assessment in under weight, normal weight, over weight and pregnant subjects for risk fector of deep vein thrombosis (DVT) - Mat Harun, Noor Hafizzatul 'Izzah (2017)
An in vivo assessment of vein mechanism on the subjects with no history of Deep Vein Thrombosis (DVT) that is categorised into different weight categories and also the pregnant subjects with the high risk factor of DVT are presented to diagnose the early stage of DVT. DVT can give serious threat to the one's health condition. The blood clot that develops in the vessel can block the blood and cause the blood to pool which can lead to pain, swelling and also permanent damage. Currently, the DVT has been diagnosed using ultrasound, which is considered to be non-invasive and low cost compared to other methods available. Thus, in this research, assessments of the blood flow velocity and measurement of the vessel wall elasticity on popliteal vein using ultrasound have been proposed. The blood flow velocity and the wall displacement are considered to be the important parameters to construct a clinical model of DVT risk factor. As a result, the vessel wall displacement for the overweight category is the highest among the others which is only 6% different from the vein displacement of DVT subject, while having the lowest blood flow velocity rate ( 1.62± 1.10 cm/s) and also highest elasticity (I.I 0±0.45 MPa) compared to the other weight category. This shows that the overweight vein mechanism has similarities to the DVT condition. Furthermore, for the pregnant subjects, it has been shown that their vessel diameter became smaller when entering the obesity category. Whilst, there are non-consistent measurement obtained from the blood flow velocity and vessel wall elasticity since they were affected by the physiological changes during their pregnancy. However, those changes did support the condition of thrombus development. Therefore, this study helps to verify the link between overweight and pregnant subjects to DVT disorder and its important in predicting the probability of DVT on human at the early stage